Translational research in genetics and genomics - Smith, Moyra (Oxford University Press, 2008)
In Translational Research in Genetics and Genomics, noted geneticist and veteran OUP author, Moyra Smith, present a comprehensive critical review of the translation of genetic and genomic research into health care. Dr. Smith's motivation for writing is driven by the gap that exists between the rather amazing discoveries in medical genetics and genomics at basic science levels and the translation to disease management in single gene disorders, specific genetic syndromes, and complex genetic diseases.